Polyphasic taxonomy of Aspergillus section Sparsi - J. Varga; J.C. Frisvad; R.A. Samson (IMA Fungus)
Aspergillus section Sparsi includes species which have large globose conidial heads with colours ranging from light grey to olive-buff. In this study, we examined isolates of species tentatively assigned to section Sparsi using a polyphasic approach. The characters examined include sequence analysis of partial β-tubulin, calmodulin and ITS sequences of the isolates, morphological and physiological tests, and examination of the extrolite profiles. Our data indicate that the revised section Sparsi includes 10 species: A. anthodesmis, A. biplanus, A. conjunctus, A. diversus, A. funiculosus, A. implicatus, A. panamensis, A. quitensis, A. sparsus, and the new taxon A. haitiensis. The recently described A. quitensis and A. ecuadorensis are synonyms of A. amazonicus based on both molecular and physiological data. The white-spored species A. implicatus has also been found to belong to this section. Aspergillus haitiensis sp. nov. is characterised by whitish colonies becoming reddish brown due to the production of conidial heads, and dark coloured smooth stipes. The taxon produces gregatins, siderin and several unknown but characteristic metabolites.